Peran Amerika Serikat Dalam Normalisasi Hubungan Arab-Israel Tahun 2020 - Aisyah, Aisyah (Department of International Relations, Universitas Mulawarman, 2020)
The normalization between the United Arab Emirates (UAE) and Bahrain with Israel in September 2020 marks a new phase in political dynamics in the Middle East. These two Gulf countries became the third and fourth Arab countries after Egypt and Jordan have a peace agreement with Israel, severally in 1979 and 1994. The normalization of the UAE and Bahrain with Israel in 2020 violates the Arab Peace Initiative that was endorsed by the Arab League in 2002 at the Beirut Summit and re-endorsed at 2007 and at 2017 that called on Israel to withdraw from the borders of Arab lands before the 1967 War as a condition of normalizing Israel's relations with all Arab countries. However, the role played by the United States through its foreign policy in the Middle East prompted the UAE and Bahrain to normalize with Israel.